Genealogies, Theology of the Seed & Revelation 12 - Daniel Trihandarkha (SAGACITY : Journal of Theology and Christian Education, 2021)
Abstract When God pronounced the promise of salvation by the seed to the fallen man, little did Adam and Eve probably knew the impact of that the instigation of divine war would have been. This war surely determining the course of life of human race in the world and also it reveals the subsequent of God’s revelation of His salvation plan for humankind. The book of Genesis itself contains the extended family line of the seed throughout history. We argue that the Book of Revelation chapter 12 contains the summary of journey of seed’s family line and things yet to come where culmination of divine war will be consummated. Theology will not merely stand in creating hypothesis based on the literature analyses, theology must give a possible thesis toward certainty to which literature (apocalypse) foreshadows toward reality in history to come. Abstraksi Ketika Tuhan menyatakan janji keselamatan lewat benih orang berdosa, kemungkinan Adam dan Hawa tidak mengetahui seberapa besar dampak penyebab terjadinya perang ilahi itu atas umat manusia. Hal ini tentu saja menentukan alur dari kehidupan umat manusia dan dunia, dan juga menyatakan penyataan Tuhan kemudian atas rencana keselamatan-Nya bagi umat manusia. Kami berargumen bahwa Wahyu pasal 12 berisi rangkuman perjalanan dari benih ini hingga halyang akan datang termasuk di antaranya puncak dari perang ilahi ini. Teologi tidak boleh hanay berdiri membuat sebuah hipotesa berdasar analisis literature semata, teologi harus dapat memberikan sebuah tesis menuju kepada kepastian yang dimana literature (apokalip) memberi bayangan kepada sebuah realita dalam sejarah yang akan datang.